Bitcoin e os desafios da tributação - Ferreira, Stéfano Vieira Machado (2023)
This thesis analyzes the Bitcoin phenomenon from the perspective of Tax Law. At first, it focuses on the elucidation of the origin and operation of the Bitcoin protocol and the bitcoin digital currency. Given the importance of the term "coin" for the work, it makes legal and economic considerations in a specific chapter. It uses the method of logical-semantic constructivism in the understanding of the legal norm, primary and secondary, and the construction of tax correction rules, as well as a lack of correction on pragmatism and its usefulness for the study of Bitcoin taxation. With these points settled, examine bitcoins operations and the understanding of the Federal Revenue Service of Brazil regarding the possibility of Income Tax of any nature, dealing with the concepts of any nature, "earnings of any nature", "capital gain" and "exchange". In chapter 5, it evaluates the possibility of taxing operations with bitcoins by the Operations Tax (IO), in the materialities credit, exchange and bonds and securities. In the next chapter, it investigates the Tax on Circulation of Goods and Services - ICMS, focusing on the concept of value and the contingency of reaching intangible goods. Bitcoin mining, both as nuances of the activity and taxation, also receives attention in its own chapter. Next, analysis the taxation of companies that offer intermediation, resolution or resolution services, called exchanges. Finally, the last chapter considers the cases, directing the execution process and the concrete challenges to be possible in the face of this new revolutionary planning. Weighing the characteristic of decentralization inherent to the software, the anonymity, and the strong control of property by the digital signature, considered eventual guaranteed unfeasibility of constriction of the good in tax executions, thus establishing new challenges for taxation